Finite-time fault-tolerant control for flutter of wing. (June 2016) - Ming-Zhou, Gao; Guo-Ping, Cai; Ying, Nan
Abstract: In this paper, we use the radial basis function neural network and the finite-time H ∞ adaptive fault-tolerant control technique to deal with the flutter problem of wings with propulsion system, which is affected by input saturation, time delay, time-varying parameter uncertainties and external disturbances. Then sensor and actuator faults are both considered in the control design. The theory content of this article includes the trajectory optimization, modeling of wing flutter and fault-tolerant controller design. The stability of the finite-time H ∞ adaptive fault-tolerant controller is theoretically proved. Finally, simulation results are given to demonstrate the effectiveness of the scheme. Highlights: Based on the trajectory optimization, we ignore the effect of temperature, and build up the motion equation of wing flutter when propulsion system is installed on the wing. Actuator and sensor and faults, as well as the effect of time delay and input saturation on wing flutter are considered. The finite-time adaptive fault-tolerant controller for flutter is designed. Simulation results indicate the viability of the methods presented in this paper.